Development of an Online Supervision Dashboard for School Counselor Burnout Monitoring in Bullying Cases: Data Analysis and Use Evaluation - Andi Zulfahmi; Jumaria Manda; Khairul Alam; Kristian Rande Salu; M. Taufik; Miftah Kurniawan (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
This study aims to develop and evaluate an online supervision dashboard as a school counselor burnout monitoring system in handling bullying cases. The research uses a Research and Development (R&D) approach with the ADDIE model which includes the stages of needs analysis, design, development, implementation, and evaluation. The research subjects consisted of 30 school counselors and 5 guidance and counseling supervisors. Data was collected through burnout questionnaires (adaptation of the Maslach Burnout Inventory), system activity logs, usability questionnaires (System Usability Scale), observations, and interviews. The results of the study show that the dashboard developed has the main features in the form of periodic burnout assessment, trend visualization, risk notification, and supervision reporting integrated with bullying case management. Quantitative analysis showed a significant decrease in burnout scores, especially in the emotional fatigue dimension (p < 0.05), after eight weeks of using the system. The usability score is in the good category, indicating that the system is easy to use and accepted by users. Qualitative findings indicate that dashboards increase counselors' self-awareness and strengthen the quality of data-driven supervision. Overall, the online supervision dashboard has the potential to be an innovation in the transformation of education supervision that supports the prevention of burnout and increases the effectiveness of handling bullying cases in schools